Advances of Heat Shock Family in Ulcerative Colitis - Gong, Min; Zhang, Fengrui; Miao, Yinglei; Niu, Junkun (Frontiers in Pharmacology, 2022)
Ulcerative Colitis (UC) is a non-specific and chronic inflammatory disease of colonic mucosa whose exact etiology and mechanisms remain unclear. The incidence rate of UC is increasing year by year worldwide. What followed is that the medical costs are also rising rapidly. Therefore, it is urgent to understand the pathogenesis and find promising therapeutic targets for UC. Intestinal mucosal homeostasis is essential for normal bowel function, and its imbalance may be an important pathogenesis of UC. Endogenous homeostatic regulators play roles in repairing intestinal mucosa injury after stress. Heat shock family proteins are essential endogenous homeostasis factors. They can inhibit inflammation, regulate intestinal epithelial cells' survival and death, and promote mucosal healing. Thus, they play important roles in sustaining intestinal mucosal homeostasis and protecting against UC progression. However, the heat shock family may promote UC carcinogenesis. Here, we summarize the advances in the research of the functions of the heat shock family in UC. And this review is an attempt to light on the etiopathogenesis of UC, highlighting the endogenous protective mechanisms, hoping to provide a novel therapeutic target for UC treatment.